Application of Molecular Topology for Predicting the Antioxidant Activity of a Group of Phenolic Compounds - Bastos, Fernando de Souza; da Silva Machado, Diogo; Barros Silva Filho, Jaime; Luiza Ferreira Delfim, Maria (Sigmae, 2024)
The study of compounds with antioxidant capabilities is of great interest to the scientific community, as it has implications in several areas, from Agricultural Sciences to Biological Sciences, including Food Engineering, Medicine, and Pharmacy. In applications related to human health, it is known that antioxidant activity can delay or inhibit oxidative damage to cells, reducing damage caused by free radicals, helping in the treatment, or even preventing or postponing the onset of various diseases. Among the compounds that have antioxidant properties, there are several classes of phenolic compounds, which include several compounds with different chemical structures. Despite their importance, identifying and predicting the antioxidant potential of phenolic compunds remains a significant challenge due to their structural diversity and the complexity of their mechanisms of action. In this work, based on the molecular branching of compounds and their intramolecular charge distributions, and using Molecular Topology, we propose a significant topological mathematical model to evaluate the potential of candidate compounds to have an antioxidant function. The advantage of the model is that it allows for efficient predictive analysis, assisting in the identification of promising compounds more quickly and accurately, which can accelerate the development of new antioxidants with therapeutic applications.